The Role of the Indonesian Air Force in Military Operations Other Than War (MOOTW) - Ari Sujatmiko; Evi Satispi; Maya Puspita Dewi; Asep Kurnia (Journal Of Social Science (JoSS), 2025)
This study examines the role of the Indonesian National Army Air Force (TNI AU) in the implementation of Non-War Military Operations (OMSP), especially in the handling of non-natural disasters of the COVID-19 pandemic at the Raden Sadjad Air Force Base, Natuna. The COVID-19 pandemic is a non-traditional security threat that requires a rapid and coordinated response from various sectors, including the military. This study uses a qualitative approach with a case study method, analyzing the role of the Indonesian Air Force based on Health Theory which includes the stages of pre-action, action, and post-action (maintenance). Data was collected through in-depth interviews with Indonesian Air Force officers, health workers, and local government officials, as well as direct observation and documentation studies. The results of the study show that the Indonesian Air Force, especially the Raden Sadjad Base, played a strategic role in the quarantine of 238 Indonesian citizens from Wuhan in February 2020, the distribution of health logistics, and coordination with various agencies. However, there are significant challenges in the form of limited regulations regarding the operational procedures of the Indonesian Air Force in dealing with non-military threats in the form of dangerous viruses, coordination between institutions that are not optimal, limited infrastructure including defense equipment that is not commensurate with the size of the area, and gaps in human resource capacity. Analysis using Health Theory revealed that the pre-action stage requires strengthening through the preparation of clear Standard Operating Procedures (SOPs) and strengthening preventive coordination,